Detailed Process of Shell Construction in the Photosynthetic Testate Amoeba Paulinella chromatophora (Euglyphid, Rhizaria). (4th March 2014) - Nomura, Mami; Nakayama, Takuro; Ishida, Ken‐ichiro
Abstract Most euglyphids, a group of testate amoebae, have a shell that is constructed from numerous siliceous scales. The euglyphid Paulinella chromatophora has photosynthetic organelles (termed cyanelles or chromatophores), allowing it to be cultivated more easily than other euglyphids. Like other euglyphids, P. chromatophora has a siliceous shell made of brick‐like scales. These scales are varied in size and shape. How a P. chromatophora cell makes this shell is still a mystery. We examined shell construction process in P. chromatophora in detail using time‐lapse video microscopy. The new shell was constructed by a specialized pseudopodium that laid out each scale into correct position, one scale at a time. The present study inferred that the sequence of scale production and secretion was well controlled.